2019
DOI: 10.1029/2018jd029222
|View full text |Cite
|
Sign up to set email alerts
|

Weak Stratospheric Polar Vortex Events Modulated by the Arctic Sea‐Ice Loss

Abstract: We characterize the differences in the upward planetary‐scale wave propagation during observed weak polar vortex (WPV) events between heavy‐ and light‐sea‐ice years in the Barents‐Kara Sea based on a composite analysis for the period of 1979–2015. Upward wave propagation during WPV events in heavy‐ice years is dominated by the wavenumber 1 component. In contrast, WPV events occurring in light‐ice years are characterized by stronger wavenumber 2 propagation, which is caused by the tropospheric wavenumber 2 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…Early modeling studies found that low sea ice, either pan-Arctic or east of Greenland and extending into the Barents-Kara seas, forced cold temperatures across the NH continents similar to the negative AO temperature pattern 91,92,93,94,95 . However, since then, modeling studies have supported the entire range of atmospheric response, including cold continents 12,69,71,105,106,112,116,120,121 , a disrupted stratospheric polar vortex comparable to observed 69,112,118,121 and weaker and/or delayed relative to observed 51,100 , a negative AO 118,122 , a positive AO 123,124 with mild continental temperatures 125 and finally no robust impact on midlatitude weather 97,98,99,126 .…”
Section: Observational Analysis Versus Modeling Experimentsmentioning
confidence: 99%
“…Early modeling studies found that low sea ice, either pan-Arctic or east of Greenland and extending into the Barents-Kara seas, forced cold temperatures across the NH continents similar to the negative AO temperature pattern 91,92,93,94,95 . However, since then, modeling studies have supported the entire range of atmospheric response, including cold continents 12,69,71,105,106,112,116,120,121 , a disrupted stratospheric polar vortex comparable to observed 69,112,118,121 and weaker and/or delayed relative to observed 51,100 , a negative AO 118,122 , a positive AO 123,124 with mild continental temperatures 125 and finally no robust impact on midlatitude weather 97,98,99,126 .…”
Section: Observational Analysis Versus Modeling Experimentsmentioning
confidence: 99%
“…In recent years, many components of this pathway have been investigated, especially concerning the increased frequency of cold winters over Europe and the emergence of the counter-intuitive "warm Arctic-cold continent" (WACC) pattern over Eurasia (Petoukhov and Semenov, 2010;Vihma, 2014). However, there remains substantial uncertainty about the impact of Arctic sea ice in terms of location (Zhang et al, 2016;Luo et al, 2017;Screen 2017;Kelleher and Screen, 2018), timing (Honda et al, 2009;Overland et al, 2011;Inoue et al, 2012;Suo et al, 2016;Sorokina et al, 2016;King et al, 2016;Screen, 2017;Wegmann et al, 2018a; or whether sea ice can be used as a predictor or forcing at all based on the contrasting results of model studies (McCusker et al, 2016;Collow et al, 2017;Pedersen et al, 2016;Boland et al, 2017;Crasemann et al, 2017;Ruggieri et al, 2017;Garcia-Serrano et al, 2017;Francis, 2017;Screen et al, 2018;Mori et al, 2019;Hoshi et al, 2019;Romanowksy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis shows the potential for combining OBP, SSH, and SST satellite data to determine monthly time series of satellite upper ocean OID steric height, heat and freshwater contents for major parts of the southern Barents Sea. This is important for the local ecosystem (Eriksen et al, 2011;Oziel et al, 2017), and the southern Barents Sea is a region where SST is correlated with anomalous winter surface air temperature across Europe and Asia (Blackport et al, 2019;Hoshi et al, 2019). This builds on Volkov et al's (2013) analysis of steric height, thermosteric height, and halosteric height using satellite data.…”
Section: Resultsmentioning
confidence: 99%
“…A significant increase in the temperature of AW entering the Barents Sea also coincided with a sea ice regime shift in the mid‐2000s, increasing the temperature gradient across the Polar Front, limiting the southward extent of winter sea ice, and resulting in warmer and saltier BSW (Barton et al., 2018). The sea ice loss (Hoshi et al., 2019; Petoukhov & Semenov, 2010) and changes in the ocean to atmospheric heat flux (Blackport et al., 2019) in the Barents and Kara Seas have been correlated with anomalous weather conditions in northern Europe, Russia, and Asia. Monitoring the variations and changes in the properties of BSW is thus relevant for understanding the atmospheric and ocean changes, locally in the Barents Sea and beyond.…”
Section: Introductionmentioning
confidence: 99%